On the Origin of the Photospheric Magnetic Field - Peter W. Schuck; Mark G. Linton; Kalman J. Knizhnik; James E. Leake (The Astrophysical Journal, 2022)
This article presents results that challenge the paradigms that (1) the convection zone is the source of the radial magnetic field in the photosphere and (2) that coronal currents are neutralized from the perspective of the photosphere. We demonstrate, using a new analysis tool applied to simulations and observations, that bare or partially dressed current channels are supported by the solar corona and that fingerprints of these coronal current systems can be detected in the photosphere. These coronal current channels can be a significant source of the radial component of the magnetic field in the photosphere. The roots of these coronal current channels in the photosphere are the source of the magnetic field component parallel to the polarity inversion line in active region NOAA 12673. These analyses and observations transform our theoretical understanding of coronal evolution and argue for a reexamination of the present paradigm in which the convection zone is the sole source of the photospheric magnetic field.